Exploring Grade 10 physical science teachers’ pedagogical approaches to the Electricity topic in selected Vryheid rural schools, KwaZulu-Natal Province - Zulu, Sphamandla Innocent (University of the Witwatersrand, Johannesburg, 2023)
In a context often characterised by lack of resources, with its peoples’ agencies often ignored, how do teachers teach difficult yet practical science topics in rural classrooms? This question was asked in a context where teaching is described as a complex task. Without overlooking teachers‘ individual agency, teaching science in rural schools is an arduous undertaking. Science teachers require sufficient and appropriate content knowledge and pedagogical knowledge for enhanced science teaching and learning experiences. Understanding teachers‘ pedagogical knowledge was the interest of this study. Therefore, the purpose of this study was to explore teachers‘ pedagogical approaches during the Electricity lessons in Grade 10 rural classrooms and examine teachers‘ pedagogical reasoning for the observed teaching approaches. The paucity of physical science education research in rural schools has not been able to offer an account of teachers‘ pedagogical approaches and what influences their pedagogical practices within rural classrooms. Hence, the current study as introductory for other science education researchers in researching physical science teaching and learning in rural schools. The present study used Mavhunga‘s (2012) topic specific pedagogical content knowledge (tsPCK) as a theoretical framework focusing on all five components of the theory. To supplement tsPCK, Scott et al.‘s. (2011) pedagogical link-making (PLM) was also used in identifying and discussing the nuances of teachers‘ pedagogical approaches during electricity lessons. I used a collective case study design and adopted a qualitative research approach and classroom observations, video-stimulated recall interviews (VSRI‘s), and semi-structured interviews as methods of data generation. The case study focused on three teachers from Vryheid rural schools in KwaZulu-Natal Province of South Africa, to investigate their classroom practices, particularly, pedagogical approaches to Electricity topic and factors that shape their teaching of the topic. The three teachers were purposefully and conveniently selected. To guide this case study investigation, the main research question of the study was: How do Grade 10 rural physical science teachers teach the Electricity topic? The findings of this study revealed that the teaching of Electricity topic requires multiple representations at symbolic, macro, and sub-microscopic levels; and that explicit links of these representations are vital for science knowledge building. Teachers used mostly symbolic level, with some teachers limitedly representing the Electricity topic macroscopically through practical work (hands-on practical work and demonstrations). Important also was the contextualized level of representations including analogies that teachers used to teach the topic. Moreover, teachers constantly worked with learners‘ prior knowledge in their facilitation methods while also considering curricular sequencing and content skills linkage made within and across the lessons. Also, some observed electricity concepts or processes proved to be difficult for teachers to teach, while, I acknowledge the various conceptual teaching approaches that teachers used to ensure deep understanding of the topic of Electricity including those concepts that seemed difficult to teach. Other observable teachers‘ approaches included the dominance of question and answer teaching approach and teacher-centered approach, with some subject-matter centered approach and limited learner-centered approach. All three teachers taught the same topic differently. During VSRI and semi-structured interviews, teachers commented on their teaching for assessment purposes. Teachers‘ pedagogical approaches were influenced by various factors including teachers‘ teaching and learning experiences, learners‘ prior knowledge, teaching for compliance, teaching for assessment (examination), availability and appropriate use of science laboratory apparatus for Electricity topic. Given the findings of this study, I recommend among other things, research intervention intending to equip rural teachers with pedagogical skills for teaching physical science topics including Electricity topic.
A thesis submitted in fulfilment of the requirement for the degree of Doctor of Philosophy (PhD) to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg.
Keywords: Electricity topic; Pedagogical approaches; Rural; Teaching; Physical science; UCTD; SDG-4: Quality education